Pike Mercury Concentration in Small Boreal Headwater Lakes During Four Decades of Regional and Local Changes - Rask, Martti; Malinen, Tommi; Nyberg, Kari; Olin, Mikko; Kurkilahti, Mika; Blauberg, Tarja-Riitta; Salonen, Maiju; Vesala, Sami; Ruuhijärvi, Jukka; Tiainen, Joni; Vuorenmaa, Jussi; Lodenius, Martin; et al. (Springer Nature, 2024)
We measured the total mercury (THg) concentration in the muscle of northern pike (Esox lucius L.) from 12 boreal headwater lakes once per decade during the 1980s to 2010s. Relations of pike THg to regional environmental changes, such as reduction of acid deposition and increase in water colour (i.e. browning), were examined as well as the effects of local lake-specific changes caused by introduced beavers (Castor canadensis) and intensive fishing of pike. No consistent decrease in pike THg took place during 1983–2013 despite the reductions in mercury emissions from European sources since the 1990s and the associated decreased mercury deposition in Finland. In most of the lakes, individual pike exceeded the recommended limit for human consumption (1 mg kg−1, wet weight). The highest THg levels were recorded in 2002 following intensive browning of the lakes in the 1990s in connection with decreased sulphate deposition. The effects of acid deposition were only seen as the highest pike THg in the two most acidic lakes in the early 1980s. After taking length effects into account, pike THg had a negative relationship with growth (i.e. growth dilution), but a positive relationship with water colour, iron, nutrients and maximum lake depth. Females grew faster and had lower THg than males. Pike THg was elevated in beaver-impacted lakes. Experimental removal of pike from three study lakes during 2005–2013 resulted in a decrease of pike THg. These findings emphasize the significance of local abiotic and biotic drivers when interpreting the regional long-term trends in pike THg.
Keywords: THg; Pike growth; Browning of lakes; Beaver; Intensive fshing